1995
DOI: 10.1007/bf03347842
|View full text |Cite
|
Sign up to set email alerts
|

The effect of constant light on the concentration of catecholamines of the hypothalamus and adrenal glands, circulatory hadrenocorticotropin hormone and progesterone

Abstract: The participation of adrenocorticotropic hormone (ACTH) in the control of adrenal glands and the regulation of ACTH secretion in female rats exposed to constant light for six weeks were studied. A significant increase of plasma ACTH (p < 0.05) in rats exposed to constant light is in correlation with an increase of epinephrine (E) synthesis in adrenal gland (p < 0.05) when compared to intact controls. On the other hand, ACTH secretion is in inverse relation with a significantly reduced concentration of dopamine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…Plasma level of ACTH was also significantly increased in the former group of animals in relation to the control value. These results are in accordance with the data of Ivani{evi}-Milo-vanovi} et al (19) who reported that the expo-sure of rat females to constant light for six weeks led to a significant increase of both plasma ACTH level and the synthesis of epinephrine in the adrenal gland. It was observed earlier that chronic exposure of adult rat females to constant light activates the stress system, namely, paraventricular ' infundibular CRH (corticotropin-releasing hormone) system (9).…”
Section: Discussionsupporting
confidence: 93%
“…Plasma level of ACTH was also significantly increased in the former group of animals in relation to the control value. These results are in accordance with the data of Ivani{evi}-Milo-vanovi} et al (19) who reported that the expo-sure of rat females to constant light for six weeks led to a significant increase of both plasma ACTH level and the synthesis of epinephrine in the adrenal gland. It was observed earlier that chronic exposure of adult rat females to constant light activates the stress system, namely, paraventricular ' infundibular CRH (corticotropin-releasing hormone) system (9).…”
Section: Discussionsupporting
confidence: 93%
“…A possibility exists that exposure to continuous overnight illumination produced the observed estrous cycle disruption in the CMS group. However, while previous studies suggest that exposure to constant light lengthens or disrupts the estrous cycle in rodents (Fiske 1941;Maric et al 1965;Cvijić et al 1998), these changes have typically been reported following chronic periods (e.g., from 2 weeks to 3 months) of constant light situations (Ivanišević-Milovanovićc et al 1995;Anisimov et al 2004). In contrast, the brief periods of continuous illumination used in the current protocol (12 h, twice weekly) likely produced minimal, if any, direct effects on the estrous cycle in female rats.…”
Section: Discussionmentioning
confidence: 94%
“…Light is a powerful synchronizer of circadian rhythms, and thus, animal facility lighting intensity and photoperiod can affect behavioral activity and metabolic homeostasis (Menaker 1976; Reiter 1991). For example, exposure to constant light affects catecholamine, ACTH, and progesterone levels, while constant darkness shifts the peaks of blood glucose and nonesterified fatty acids and alters the expression of catabolic enzymes (Ivanisevic-Milovanovic et al 1995; Zhang et al 2006). Even small changes to the normal light/dark cycles, such as a switch to daylight savings time or a brief light pulse during the dark phase, can cause temporary misalignment of behavioral and metabolic rhythmicity, potentially increasing variability in experimental results (Clough 1982).…”
Section: Perspectives On Timing In Animal and Human Studiesmentioning
confidence: 99%